Cathepsin K+ Non-Osteoclast Cells in the Skeletal System: Function, Models, Identity, and Therapeutic Implications - Zou, Nanyu; Liu, Ran; Li, Changjun (Frontiers in Cell and Developmental Biology, 2022)
Cathepsin K (Ctsk) is a cysteine protease of the papain superfamily initially identified in differentiated osteoclasts; it plays a critical role in degrading the bone matrix. However, subsequent in vivo and in vitro studies based on animal models elucidate novel subpopulations of Ctsk-expressing cells, which display markers and properties of mesenchymal stem/progenitor cells. This review introduces the function, identity, and role of Ctsk+ cells and their therapeutic implications in related preclinical osseous disorder models. It also summarizes the available in vivo models for studying Ctsk+ cells and their progeny. Further investigations of detailed properties and mechanisms of Ctsk+ cells in transgenic models are required to guide potential therapeutic targets in multiple diseases in the future.